Macroinvertebrados como indicadores de qualidade de água no reservatório do Rio Passaúna, PR, Brasil - Ferraresi, Ana Camila dos Santos (2015)
Biological indicators are being increasingly used, together with physical and chemical indicators, in water quality assessments in rivers, lakes, reservoirs and other natural water bodies. Macroinvertebrates consist of a key group of bioindicators thanks to their responsiveness to environmental changes. In this sense, this study was focused on the use of macroinvertebrates as water quality bioindicators for the Passaúna reservoir, situated in the Passaúna river watershed, in the metropolitan region of Curitiba, Paraná state, Brazil. The characterisation work was undertaken with five field sampling campaings over the rain and dry seasons, between April and December 2014, and subsequent analysis of the benthic and periphytic communities. A total of 193 benthic organisms were found, divided in six taxa. The periphytic community identified consisted of 600 organisms divided in 17 taxa. The benthic community was mostly composed of Chironomidae, which represented 61% of the sample total, while for the periphytic community Hyalellidae represented 72% of the sampled individuals. Water quality, as determined through physical and chemical parameters indicated that the reservoir is moderately degraded. This was generally confirmed by the water quality analysis based on the macroinvertebrate indexes. This study led to the first known macroinvertebrate database for the Passaúna reservoir. However, a more comprehensive application of such information in water quality assessments of the water body requires further research aimed at creating/adapting a specific macroinvertebrate-based biomonitoring index.